RANCANG BANGUN SISTEM DETEKTOR KESALAHAN PADA PEMASANGAN KOMPONEN PCB BERBASIS ARDUINO - Mulia, Ramdi Mulia; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2022)
The number of PCB damage at PT. PCI ELKTRONIK INTERNATIONAL is the trigger for the loss to the company, it is because it is influenced by the production process, especially in the production of component installation parts to PCBs that do not yet have a detection device or detector system in the company with that process of installing components to the PCB. there are many installation errors (human error), with the event a tool was designed entitled Design of an Error Detector System on Arduino-Based PCB Component Installation, this tool was designed using Arduino Uno R3, ATMega 328p Microcontroller, four sr04 Ultarsonic Sensors, and LCD 2x16. With this tool the process of taking components is carried out with a sequence system starting from sensor A, to sensor B, to sensor C, and to sensor D, this process will be detected by the ultrasonic sensor sr04 if an error occurs in taking or taking not sequential, then the LCD will display information error (Wrong), and if the retrieval process is in sequence, the LCD displays correct information (PASS). This tool aims to minimize errors in the process of installing components to the PCB.